Role Of Cyclooxygenases In Zebrafish Oogenesis And Their Transcriptional Regulation By Peroxisome Proliferator Activated Receptor Gamma - Khare, Vani (2013)
Prostaglandins are required for the successful development and functioning of the female reproductive system in vertebrates. The synthesis of prostaglandin relies on the catalytic activities of two cyclooxygenase isoforms (COX-1 and COX-2). Various reports emphasize that both COX isoforms are essential for the production of prostaglandin during various stages of oogenesis, such as oocyte growth, maturation and ovulation. In comparison to COX-2, there is a paucity of knowledge on the role of COX-1, especially in oogenesis. At the same time, while COX-2 is a well established marker in ovulation, its function in growth and maturation of oocyte requires further exploration. This study, thereby, distinguishes the role of COX-1 and COX-2 during zebrafish oocyte growth and maturation, firstly by examining the mRNA expression of both the isoforms in these oocyte stages. An increase in zebrafish follicle COX-1 mRNA expression was observed as the oocytes develop and mature.